UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA DALAM MERANCANG MEDIA PEMBELAJARAN BERBASIS TIK MELALUI KEGIATAN LESSON STUDY - Syahrul Munir (Jurnal Pendidikan Ekonomi, 2018)
enthusiastic in expressing ideas in developing ICT-based learning media. The solution given to overcome this is by applying Lesson Study activities in learning. The purpose of this study is to determine the ability of creative thinking students majoring in development economics in developing ICT-based learning media through the action of lesson study. This research was conducted by the team of lesson study team which consisted of four lecturers who acted as model and observer lecturers, followed by 25 students majoring in development economics who took the course of learning media development. This research took place in three class action cycles. The first cycle uses mind mapping based learning, the second cycle uses group discussion based learning, and the third use individual based learning. Instruments used in the form of observation sheet given at each learning cycle. The result of this research is the application of several strategies in learning, development of several learning instruments to assess the dependent variable. Application of lesson study in learning can increase the level of students' creative thinking in developing ICT-based learning media. DOI: https://dx.doi.org/10.17977/UM014v11i12018p048